Vitamin D status of adult females residing in Ballabgarh health and demographic surveillance system: A community-based study - Puneet Misra; Rahul Srivastava; Anoop Misra; Shashi Kant; Priyanka Kardam; Naval K Vikram (Wolters Kluwer Medknow Publications, 2017)
Background: Vitamin D deficiency (VDD) is widespread, yet it is the most underdiagnosed and undertreated nutritional deficiency in the world. The prevalence of VDD is estimated to affect over 1 billion people worldwide. Objectives: The present study was conducted to estimate the prevalence of VDD among adult females aged 20-60 years residing in a rural community of North India, and to find its association with various sociobehavioral risk factors. Methods: The present study is an analytical cross-sectional study conducted among females aged 20-60 years in rural Ballabgarh. Four hundred women were randomly selected from one of the villages of the Health and Demographic Surveillance System. Semi-structured, pretested interview schedule was administered to the study participants. Fasting venous blood sample was collected for the measurement of plasma sugar level and Vitamin D (25-hydroxyvitamin D). Results: The prevalence of VDD was 90.8% (95% confidence interval [CI] - 87.5-93.3), while that of Vitamin D insufficiency was 8.9% (95% CI - 6.4-12.2). On logistic regression analysis, 24 h calorie intake, protein intake, and prediabetes status of the participants were significantly associated with VDD. Conclusion: Very high prevalence of VDD was observed among the females (20-60 years) residing in rural Ballabgarh.